Towards Reverse Transcription with an Expanded Genetic Alphabet. (3rd May 2019) - Eggert, Frank; Kurscheidt, Katharina; Hoffmann, Eva; Kath‐Schorr, Stephanie
Abstract: Unnatural base pairs (UBPs) strikingly augment the natural genetic alphabet. The development of particular hydrophobic UBPs even allows insertion and stable propagation in bacteria. Those UBPs expand the chemical scope of DNA and RNA, and thus, could enable the evolution of novel aptamers or ribozymes by in vitro selection (systematic evolution of ligands by exponential enrichment, SELEX). However, the application of such UBPs in reverse transcription (rtc), which is a key step for RNA‐based SELEX, has not been reported so far. The implication of Romesberg's NaM:TPT3 base pair in rtc reactions is presented by testing five commercially available reverse transcriptases (RTs). The employed RTs predominantly pause at the site of the unnatural nucleotide rTPT3 not being able to accept the dNaM building block as a substrate. This allows verification of the unnatural base position in RNA and an estimation of their abundance. In contrast, primer extension from an rNaM‐containing template results in considerably more full‐length cDNA. Furthermore, RTs that could potentially be able to handle an expanded genetic alphabet based on NaM:TPT3 are presented. Abstract : Stop or go? Unnatural base pairs expand the chemical scope of DNA and RNA. The implication of the Romesberg NaM:TPT3 base pair in reverse transcription reactions is presented by testing five commercially available reverse transcriptases (RTs). These RTs show diverse abilities to handle an expanded genetic alphabet.